The Influence of Leverage, Firm Size and Financial Distress on Accounting Conservatism - DARMAYANTI, Novi; AFRICA, Laely Aghe; SARI, A.A Pt. Agung Mirah Purnama; SUHARDIYAH, Martha (Journal of Tourism Economics and Policy, 2023)
This study aims to determine the effect of leverage, firm size, and financial distress on accounting conservatism partially or simultaneously. This study uses an observation period of 2016-2020 with purposive sampling method obtained a sample of 8 companies. The data analysis method used in this research is multiple linear regression test. The variables used are leverage, firm size, and financial distress as independent variables. While the variable of accounting conservatism as the dependent variable. The results of this study resulted in the finding that partially leverage is significant on accounting conservatism. Firm size has no significant effect on conservatism and financial distress has a significant effect on accounting conservatism. Simultaneously, leverage, firm size, and financial distress have a significant effect on accounting conservatism.